Expansion of host range for Clinostomum marginatum (Rudolphi, 1819) (Digenea: Clinostomidae) in the Brazilian Amazon - Chagas-de-Souza, Darlison (2025)
Parasites of the genus Clinostomum Leidy, 1856, are widely distributed across all continents and can infect vertebrates from various groups. In fish, they are known as causative agents of "white spot disease," which, in some cases, may lead to host mortality. Reports of new hosts for these trematodes have been steadily increasing. In this context, the present study documents new host Acestrorhynchus falcirostris (Cuvier, 1819) for the species Clinostomum marginatum(Rudolphi, 1819) and contributes to understanding its distribution in the Brazilian Amazon.